Vibration spectroscopic technique for species identification based on lipid characteristics - Fei, Gao; Lujia, Han; Xian, Liu (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Due to the widespread of adulteration of lipid in food and feed industry, the quality and safety of lipid are of public concern gradually. Firstly, the current article presents theory and mechanism of species identification of lipid by spectroscopic technique. Potential of near-infrared reflectance spectroscopy (NIR), Fourier transform infrared spectroscopy (FT-IR), and Fourier transform Raman spectroscopy (FT-Raman) applied to species identification of lipid were summarized. In addition, the relationship between lipid and spectroscopy as well as the recent advances of species identification of lipid were discussed. Research showed that FT-IR and FT-Raman spectroscopies possessed more efficient potential for species identification of lipid. Finally, prospects for future lipid detection and relative practical application, and combination of spectroscopy and other technique were further discussed.Keywords: feedstuff, fatty acid, NIR, FT-IR, FT-Raman spectroscopyDOI: 10.3965/j.ijabe.20171003.3144Citation: Gao F, Han L J, Liu X. Vibration spectroscopic technique for species identification based on lipid characteristics. Int J Agric & Biol Eng, 2017; 10(3): 255–268.